Advanced Glycation End Products (AGEs) and their Receptor (RAGE) System in Diabetic Retinopathy - Yamagishi, Sho-ichi; Nakamura, Kazuo; Matsui, Takanori (Current Drug Discovery Technologies, 2006)
Vascular complications are a leading cause of blindness, end-stage renal failure, a variety of neuropathies and accelerated atherosclerosis, which could account for disabilities and high mortality rates in patients with diabetes. There is a growing body of evidence that formation and accumulation of advanced glycation end products (AGEs) progress during normal aging, and at an extremely accelerated rate in diabetes, thus being involved in the pathogenesis of diabetic vascular complications. Furthermore, the interaction by AGEs of their receptor, RAGE, activates down-stream signaling and evokes inflammatory responses in vascular wall cells. Therefore, inhibition of AGE formation or blockade of the RAGE signaling may be a promising target for therapeutic intervention to prevent diabetic vascular complications. This review discusses the molecular mechanisms of diabetic retinopathy, especially focusing on the AGE-RAGE system. Several types of inhibitors of the AGE-RAGE system and their therapeutic implications are also reviewed here.
Keywords: Diabetic retinopathy